Learning Strategies at SD Muhammadiyah 1 Waru During Covid-19 Pandemic - Indah Permatasari (International Consortium of Education and Culture Research Studies, 2021)
This study aims to analyze the various learning strategies implemented by Muhammadiyah 1 Waru Elementary School in the midst of the Covid-19 outbreak that is hitting Indonesia. Where because of the outbreak it also affects education in Indonesia so that the Ministry of Education and Culture issued a policy that learning is done online. The method used in this research is descriptive qualitative research. It means that the desired result is in the form of a complete description or description of the research facts. The results showed that the implementation of the learning strategy set by the teachers at Muhammadiyah 1 Waru Elementary School was good, where the teacher used the google meet, whatsapp, and zoom applications in the delivery of learning material. In online learning, parents also act as facilitators for the implementation of learning.